2018
DOI: 10.1186/s12917-018-1720-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative features of infections of two Massachusetts (Mass) infectious bronchitis virus (IBV) variants isolated from Western Canadian layer flocks

Abstract: BackgroundInfectious bronchitis virus (IBV) is one of the leading causes of mortality and morbidity in chickens. There are numerous serotypes and variants, which do not confer cross protection resulting in failure of currently used IBV vaccines. Although variant IBV isolates with major genetic differences have been subjected to comparative studies, it is unknown whether minor genetic differences in IBV variants within a serotype are different in terms of pathogenesis and eliciting host responses. Two Massachus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 72 publications
(101 reference statements)
1
11
0
Order By: Relevance
“…The S1 sequences of the isolates LJL/130906 and I1124/16 showed obvious point mutations when compared with those of the M41 and H120 strains ( Xu et al, 2018 ), however, other genes and regions were found to be affected by mutations in the genomes of Mass-type strains which was consistent with previous observations ( Amarasinghe et al, 2018 ). It is important to note that the sequence of the S1 subunit in the isolate I1124/16 was identical to that of the 14 Mass-type IBV strains in America and a Thailand strain.…”
Section: Discussionsupporting
confidence: 90%
“…The S1 sequences of the isolates LJL/130906 and I1124/16 showed obvious point mutations when compared with those of the M41 and H120 strains ( Xu et al, 2018 ), however, other genes and regions were found to be affected by mutations in the genomes of Mass-type strains which was consistent with previous observations ( Amarasinghe et al, 2018 ). It is important to note that the sequence of the S1 subunit in the isolate I1124/16 was identical to that of the 14 Mass-type IBV strains in America and a Thailand strain.…”
Section: Discussionsupporting
confidence: 90%
“…Although the classification of IBV variants based on partial or full S1 gene sequences is feasible, in depth molecular analysis of IBV variants requires the examination of the complete genome of the IBV. Previously, two Mass IBV variants isolated from western Canada were characterized using whole genome sequencing [20]. In the current study, the genomic makeup of DMV/1639-like isolates from diagnostic samples are characterized in detail, and several potential recombination sites are identified.…”
Section: Introductionmentioning
confidence: 99%
“…IBV causes upper respiratory illness, nephritic syndrome, and a drop in egg production in layer chickens [1]. The mortality rate can be high in young chickens, especially with other secondary complications such as viral and bacterial infections [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%